2015
DOI: 10.3382/ps/pev292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various fiber types and choice feeding of fiber on performance, gut development, humoral immunity, and fiber preference in broiler chicks

Abstract: Two experiments were conducted to investigate the effect of fibrous materials with one single diet or by choice feeding on performance, intestinal morphology, immunity, and fiber preference in broiler chicks. In experiment 1, 240-day-old chicks (Ross 308) were assigned to one of 4 treatments, comprising 5 replicates per treatment in a completely randomized design. Dietary treatments included: a basal diet (control) or 30 g/kg sugar beet pulp (SBP), 30 g/kg rice hull (RH), or 30 g/kg equal combination of them (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 39 publications
7
51
0
4
Order By: Relevance
“…There have been many studies on the effect of DF concentrations on broiler performance, but fail to be consistent across studies. Sadeghi, Toghyani, and Gheisari () observed that 30 g/kg DF sources from sugar beet pulp and rice hulls in the diet reduced daily weight gain in broiler chicks from 1 to 14 days. Conversely, diets containing 3% oat hulls increased body weight gain or ADG in broiler (Jiménezmoreno, Gonzálezalvarado, Gonzálezserrano, Lázaro, & Mateos, ; Mateos, Jimenezmoreno, Serrano, & Lázaro, ), and even 2.5%–5% DF in the diet had no significant effect on ADG in young broiler.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the effect of DF concentrations on broiler performance, but fail to be consistent across studies. Sadeghi, Toghyani, and Gheisari () observed that 30 g/kg DF sources from sugar beet pulp and rice hulls in the diet reduced daily weight gain in broiler chicks from 1 to 14 days. Conversely, diets containing 3% oat hulls increased body weight gain or ADG in broiler (Jiménezmoreno, Gonzálezalvarado, Gonzálezserrano, Lázaro, & Mateos, ; Mateos, Jimenezmoreno, Serrano, & Lázaro, ), and even 2.5%–5% DF in the diet had no significant effect on ADG in young broiler.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the combined effect of lighter BW at the onset of egg production and reduced ADFI early in the egg cycle resulted in lower egg production in these pullets (Leeson et al, 1997;Pérez-Bonilla et al, 2012a In this respect, Almirall et al (1997) reported a reduction in egg production in hens fed a cereal-soybean meal diet diluted with 7.5 or 15.0% SBP, although in this research all hens received a common feeding program during the rearing phase. Similar reduction in BWG and feed efficiency has been reported in broilers by González-Alvarado et al (2010) and Sadeghi et al (2015) with the inclusion of 3% SBP in the diet. Sadeghi et al (2015) reported also an increase in intestinal viscosity and a reduction in villus height of the duodenum and ileum mucosa when 3% SBP was included in the diet.…”
Section: Hen Productivity and Egg Qualitysupporting
confidence: 62%
“…Similar reduction in BWG and feed efficiency has been reported in broilers by González-Alvarado et al (2010) and Sadeghi et al (2015) with the inclusion of 3% SBP in the diet. Sadeghi et al (2015) reported also an increase in intestinal viscosity and a reduction in villus height of the duodenum and ileum mucosa when 3% SBP was included in the diet. The fiber fraction of SBP is more soluble than that of straw (Brøkner et al, 2012;Bach Knudsen, 2014).…”
Section: Hen Productivity and Egg Qualitysupporting
confidence: 62%
See 2 more Smart Citations